2017
DOI: 10.1038/s41598-017-00949-4
|View full text |Cite
|
Sign up to set email alerts
|

Agarose Spot as a Comparative Method for in situ Analysis of Simultaneous Chemotactic Responses to Multiple Chemokines

Abstract: We describe a novel protocol to quantitatively and simultaneously compare the chemotactic responses of cells towards different chemokines. In this protocol, droplets of agarose gel containing different chemokines are applied onto the surface of a Petri dish, and then immersed under culture medium in which cells are suspended. As chemokine molecules diffuse away from the spot, a transient chemoattractant gradient is established across the spots. Cells expressing the corresponding cognate chemokine receptors mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 69 publications
0
24
0
Order By: Relevance
“…To analyze the migration capacity of the pbMSC lines under cytokine stimulation, we carried out the migration tests for a short period (48 hr) to ensure the maintenance of a chemoattractant's concentration gradient under the agarose spot. Ahmed et al (2017) have recently reported that the chemokine peptide begins to leak out as soon as the agarose spot is immersed in medium creating a transient concentration gradient that will thereafter slowly vanish. The inflammatory cytokine TNF‐α did not induce migration of any of the mesenchymal lines studied compared with the control in PBS, but a reduction in cell migration was observed for bmpbMSC‐80 and bmpbMSC‐84, cell lines isolated after G‐CSF mobilization from bone marrow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To analyze the migration capacity of the pbMSC lines under cytokine stimulation, we carried out the migration tests for a short period (48 hr) to ensure the maintenance of a chemoattractant's concentration gradient under the agarose spot. Ahmed et al (2017) have recently reported that the chemokine peptide begins to leak out as soon as the agarose spot is immersed in medium creating a transient concentration gradient that will thereafter slowly vanish. The inflammatory cytokine TNF‐α did not induce migration of any of the mesenchymal lines studied compared with the control in PBS, but a reduction in cell migration was observed for bmpbMSC‐80 and bmpbMSC‐84, cell lines isolated after G‐CSF mobilization from bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…short period (48 hr) to ensure the maintenance of a chemoattractant's concentration gradient under the agarose spot Ahmed et al (2017). have recently reported that the chemokine peptide begins to leak out as soon as the agarose spot is immersed in medium creating a transient concentration gradient that will thereafter slowly vanish.…”
mentioning
confidence: 99%
“…Agarose spot assay was performed following the protocols described previously [ 33 35 ]. Low-melting agarose (Sigma-Aldrich) was diluted into PBS to make a 1% agarose solution and then autoclaved.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, in view of CCR7 being a negative prognostic factor for lymph node (LN) metastasis, [19][20][21] our findings suggests that hypoxia is likely to contribute to the development of a metastatic phenotype in head and neck cancers through upregulation of CCR7 signalling. Therefore, inhibition of CCR7 signalling by small molecule CCR7 antagonists [60] may prove to be a very useful adjunct therapy to be used in combination with existing treatments for head and neck cancers.…”
Section: Discussionmentioning
confidence: 99%